Fortalecimiento de potencialidades ambientales para las buenas prácticas ambientales en la I.E Javier Ocampo Ruiz N°00623 Azunguilo Elías Soplin Vargas - Ponce Garcia, Sarita Magaly (2014)
The planet crosses for an evident environmental degradation. Before it, there becomes evident the need to achieve a population that it has the aptitudes adapted to face these challenges and to find solutions. If we wish that Peru could pass along the way towards the sustentabilidad there is imperious a strategy of education and communication that promotes the knowledge, values, attitudes of responsibility and respect, unavoidable to achieve a better environment. The Environmental Education (EA) is a process that consists of recognizing values and of clarifying concepts in order to promote and to form attitudes and indispensable aptitudes for understanding and estimating the interactions between the man, his culture and his halfbiophysicist. Itis so in the present Project One sought To strengthen the environmental potentials with the purpose of improving the good environmental practices of the students of the Educational Institution " Javier Ocampo Ruiz N ° 00623 Azunguillo, managing thus to sensitize the students of primary on the impact that there ha ve the actions of the human beings in the environment, increasing the Environmental Conscience.